Rapid Manufacturing of Highly Cytotoxic Clinical-Grade SARS-CoV-2-specific T Cell Products Covering SARS-CoV-2 and Its Variants for Adoptive T Cell Therapy - Bonifacius, Agnes; Tischer-Zimmermann, Sabine; Santamorena, Maria Michela; Mausberg, Philip; Schenk, Josephine; Koch, Stephanie; Barnstorf-Brandes, Johanna; Gödecke, Nina; Martens, Jörg; Goudeva, Lilia; Verboom, Murielle; Wittig, Jana; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: Evaluation of the feasibility of SARS-CoV-2-specific T cell manufacturing for adoptive T cell transfer in COVID-19 patients at risk to develop severe disease. Methods: Antiviral SARS-CoV-2-specific T cells were detected in blood of convalescent COVID-19 patients following stimulation with PepTivator SARS-CoV-2 Select using Interferon-gamma Enzyme-Linked Immunospot (IFN-γ ELISpot), SARS-CoV-2 T Cell Analysis Kit (Whole Blood) and Cytokine Secretion Assay (CSA) and were characterized with respect to memory phenotype, activation state and cytotoxic potential by multicolor flow cytometry, quantitative real-time PCR and multiplex analyses. Clinical-grade SARS-CoV-2-specific T cell products were generated by stimulation with MACS GMP PepTivator SARS-CoV-2 Select using CliniMACS Prodigy and CliniMACS Cytokine Capture System (IFN-gamma) (CCS). Functionality of enriched T cells was investigated in cytotoxicity assays and by multiplex analysis of secreted cytotoxic molecules upon target recognition. Results: Donor screening via IFN-γ ELISpot allows for pre-selection of potential donors for generation of SARS-CoV-2-specific T cells. Antiviral T cells reactive against PepTivator SARS-CoV-2 Select could be magnetically enriched from peripheral blood of convalescent COVID-19 patients by small-scale CSA resembling the clinical-grade CCS manufacturing process and showed an activated and cytotoxic T cell phenotype. Four clinical-grade SARS-CoV-2-specific T cell products were successfully generated with sufficient cell numbers and purities comparable to those observed in donor pretesting via CSA. The T cells in the generated products were shown to be capable to replicate, specifically recognize and kill target cells in vitro and secrete cytotoxic molecules upon target recognition. Cell viability, total CD3+ cell number, proliferative capacity and cytotoxic potential remained stable throughout storage of up to 72h after end of leukapheresis. Conclusions: Clinical-grade SARS-CoV-2-specific T cells are functional, have proliferative capacity and target-specific cytotoxic potential. Their function and phenotype remain stable for several days after enrichment. The adoptive transfer of partially matched, viable human SARS-CoV-2-specific T lymphocytes collected from convalescent individuals may provide the opportunity to support the immune system of COVID-19 patients at risk for severe disease.